2016
DOI: 10.14257/ijmue.2016.11.11.12
|View full text |Cite
|
Sign up to set email alerts
|

The Compensation for Distorted WDM Signals in the Optical Long-Haul Transmission Link with the Artificially Distributed Lengths of Single Mode Fiber and Residual Dispersion Per Span

Abstract: The possibility of the flexible configuration of dispersion-managed optical links combined with optical phase conjugation by adopting an artificial distribution of the lengths of single mode fiber (SMF) and residual dispersion per span (RDPS) of the fiber spans has been numerically investigated. We confirmed that 'DA-DA' patterni.e., the lengths of SMF and RDPS around the front and the rear of OPC are smaller, but the lengths of SMF and RDPS closer to the transmitter and the receiver are largeris the best arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…One approach to supplement the incomplete compensation by the difficulty of symmetry in MSSI is the combination of DM link configuration [6,7]. Authors have also confirmed the compensation improvement of 960 Gb/s wavelength division multiplexed (WDM) transmission in MSSI-based DM link [13][14][15]. In our researches related with the applying MSSI into DM link, the various DM configurations have been proposed by using non-uniform RDPSs, such as artificial distribution of arbitrary RDPSs, random distribution of various RDPSs, and asymmetric dispersion map with respect to midway OPC, to expand flexibility of link configuration.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…One approach to supplement the incomplete compensation by the difficulty of symmetry in MSSI is the combination of DM link configuration [6,7]. Authors have also confirmed the compensation improvement of 960 Gb/s wavelength division multiplexed (WDM) transmission in MSSI-based DM link [13][14][15]. In our researches related with the applying MSSI into DM link, the various DM configurations have been proposed by using non-uniform RDPSs, such as artificial distribution of arbitrary RDPSs, random distribution of various RDPSs, and asymmetric dispersion map with respect to midway OPC, to expand flexibility of link configuration.…”
Section: Introductionmentioning
confidence: 86%
“…All fiber spans include SSMF and DCF, and the length of SSMF is fixed to 80 km. The previous researches have shown that the deployment of fibers in a fiber spans affects the compensation of the distorted each channel [13]- [15]. The compensation is more increased when the arrangement of SSMF and DCF is to be symmetric with respect to OPC, that is, the arrangement order of two fibers in fiber span is different with each half link.…”
Section: Dispersion-managed Linkmentioning
confidence: 99%